Optimizing online teaching effectiveness in elementary education: Exploring multifaceted pathways based fsQCA analysis - Xiaofang Ma (PLoS ONE, 2026)
The effectiveness of online teaching has emerged as a critical concern during the COVID-19 pandemic, with a particular emphasis on fostering a sustained interest in online instruction among educators. This study employs fuzzy-set qualitative comparative analysis (fsQCA) to investigate the complex causal relationships that underpin the online teaching efficacy of elementary school teachers. A comprehensive questionnaire was administered to 171 elementary school teachers, capturing their perspectives across six key dimensions: the acceptability of online teaching, teachers’ Technological Pedagogical Content Knowledge (TPACK), students’ autonomous learning, teacher-student interaction, course design and implementation, and technological support for teaching. The findings reveal a multiplicity of configurations that contribute to enhanced online teaching effectiveness, with teachers’ acceptance of online teaching and their TPACK being identified as central conditions, pivotal for the improvement of online teaching effectiveness.